Sengketa Resep Ayam Goreng sebagai Rahasia Dagang dalam Usaha Kuliner di Indonesia - Catharina Jean Sinaga; Ni Komang Irma Adi Sukmaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Trade secrets are a type of Intellectual Property Right that plays a crucial role in providing legal protection for business information with economic value and kept confidential by its owner. In the food industry, recipes not only serve as production guidelines but also serve as a business's identity and competitive advantage. Legal issues can arise if the recipe is used or owned by others without permission, especially when conflicts arise within the business or during competition. This situation can trigger trade secret disputes that can be detrimental to business owners, both financially and sustainably. This article discusses the position of fried chicken recipes as trade secrets in culinary business practices in Indonesia and the forms of legal protection available to rights holders. The discussion was conducted based on the provisions of Law Number 30 of 2000 concerning Trade Secrets, using a normative approach. The analysis shows that a fried chicken recipe falls into the trade secret category if it meets the requirements of being unknown to the public, having economic value, and being strictly maintained by the business owner. Therefore, legal protection for trade secrets is crucial to prevent unfair business competition and provide legal certainty and protection for culinary businesses in Indonesia